2022
DOI: 10.3389/fpls.2022.993215
|View full text |Cite
|
Sign up to set email alerts
|

Functions of autophagy in chloroplast protein degradation and homeostasis

Abstract: Chloroplasts are defining organelles in plant and algae, which carried out various critical metabolic processes, including photosynthesis. Roles of chloroplast protein homeostasis in plant development and stress adaptation were clearly demonstrated in previous studies, and its maintenance requires internal proteases originated from the prokaryotic ancestor. Recently, increasing evidence revealed that eukaryotic proteolytic pathways, ubiquitin-proteasome system (UPS) and autophagy, are also involved in the turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…Plastid degradation through autophagy has been intensively analyzed in Arabidopsis thaliana ; it is divided into two types: a piecemeal type in which a portion of the plastid is degraded by autophagy ( Ishida et al., 2008 ; Wang et al., 2013 ; Michaeli et al., 2014 ), and autophagic degradation of entire plastids ( Wada et al., 2009 ; Izumi et al., 2017 ; Nakamura et al., 2018 ). These types of plastid degradation are both dependent on ATG5 activity ( Ishida et al., 2008 ; Wang et al., 2013 ; Michaeli et al., 2014 ; Izumi et al., 2017 ; Nakamura et al., 2018 ) and responsible for normal stress responses ( Izumi and Nakamura, 2018 ; Zhuang and Jiang, 2019 ; Wan and Ling, 2022 ); however, it remains unclear whether autophagy of plastids is involved in cellular differentiation. In this study, we showed that in M. polymorpha , ATG5-dependent autophagic degradation of a portion of the plastid occurs during differentiation from the spermatid to the spermatozoid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plastid degradation through autophagy has been intensively analyzed in Arabidopsis thaliana ; it is divided into two types: a piecemeal type in which a portion of the plastid is degraded by autophagy ( Ishida et al., 2008 ; Wang et al., 2013 ; Michaeli et al., 2014 ), and autophagic degradation of entire plastids ( Wada et al., 2009 ; Izumi et al., 2017 ; Nakamura et al., 2018 ). These types of plastid degradation are both dependent on ATG5 activity ( Ishida et al., 2008 ; Wang et al., 2013 ; Michaeli et al., 2014 ; Izumi et al., 2017 ; Nakamura et al., 2018 ) and responsible for normal stress responses ( Izumi and Nakamura, 2018 ; Zhuang and Jiang, 2019 ; Wan and Ling, 2022 ); however, it remains unclear whether autophagy of plastids is involved in cellular differentiation. In this study, we showed that in M. polymorpha , ATG5-dependent autophagic degradation of a portion of the plastid occurs during differentiation from the spermatid to the spermatozoid.…”
Section: Discussionmentioning
confidence: 99%
“…During spermiogenesis in M. polymorpha , the loss of function of Mp ATG5 did not substantially affect the number of plastids ( Figure 2A ), suggesting that piecemeal plastid degradation occurs in spermatids undergoing spermiogenesis. Although several cargoes for the piecemeal-type autophagic degradation of plastids have been reported ( Izumi and Nakamura, 2018 ; Zhuang and Jiang, 2019 ; Wan and Ling, 2022 ), it remains unknown which components of the plastid are degraded by autophagy during spermiogenesis in M. polymorpha . Although plastid DNA is eliminated during spermiogenesis in M. polymorpha , autophagy is unnecessary for this process, indicating that plastid DNA is not a direct target of autophagy ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transportation of SSGL bodies is dependent on ATG proteins and was demonstrated with experiments in atg mutants under dark conditions, where starch content was increased, proving the importance of autophagy in degradation of SSGL bodies (Malinova et al., 2018; Wang et al., 2013). The recognition of SSGL bodies share similarities with RCBs, where starch molecules are released through stromules (Wan & Ling, 2022). Importantly, the presence of the marker granule‐bound starch synthase I (GBSSI) distinguished SSGL bodies and its interaction with ATG8 is observed in the autophagosomal membrane (Wang et al., 2013).…”
Section: The Autophagy Mechanismmentioning
confidence: 99%
“…Two main types of chloroplast autophagy (or called chlorophagy) have been revealed: bulk degradation of Rubisco‐containing bodies during dark‐induced senescence (Ishida et al , 2008; Wada et al , 2009), and degradation of whole photodamaged chloroplasts (Izumi et al , 2017; Nakamura et al , 2018). However, little is known about the roles of selective autophagy in regulating chloroplast proteins (Otegui, 2018), and selective chlorophagy receptors or adaptors have not been identified (Kirkin & Rogov, 2019; Wan & Ling, 2022), with the exception of ATI1, a potential receptor for chloroplast degradation (Avin‐Wittenberg et al , 2012; Michaeli et al , 2014). Moreover, the role of chloroplast autophagy in various abiotic stress, such as heat and UVB, is poorly understood.…”
Section: Introductionmentioning
confidence: 99%